Juridical Review of Decriminalization on Efforts to Cut Drugs Users’ Addiction In Indonesia - Haniyah; M. Hidayat (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
As a developing country with a large population and strategic location , Indonesia has become market place for world's drug circulation. The number of victims is higher year by year. Drug victims are victims of abuse of narcotics that basically violate government regulations. So far, drug addicts in Indonesia are subject to criminal sanctions, yet from year to year the criminal sanctions applied to the victims of drug addicts have not decreased even on the contrary increasing sharply causing the emergence of drug emergency in Indonesia. The present research applies normative juridical review by providing descriptive analysis based on the data so as to provide arguments on realities that exist to provide an overview of solution. The government continues to reduce the number of victims of drug addicts, through the implementation of government decriminalization policy for victims of drug abuse and government policy on the implementation of the obligation to report for drug addicts to the receiving institutions for obtaining rehabilitation. Decriminalization policy has not been able to break the circulation of the drug chain in Indonesia as there are other factors that have not been able to be performed optimally in breaking the circulation of drugs in Indonesia.